Screening Intimate Partner Violence During Pregnancy in Maternity Clinics—Views of Finnish Public Health Nurses - Lähteenmäki, Elina; Leino‐Kilpi, Helena; Mishina, Kaisa (Wiley, 2025)
Background: Intimate partner violence (IPV) is one of the most common forms of violence against women, occurring across social classes and religions worldwide. Globally, nearly one in three women have experienced IPV in their lifetime. During pregnancy, prevalence rates range from 2.0% to 13.5%.
Aim: This study aimed to analyse the views of public health nurses (PHN) on screening for IPV in Finnish maternity clinics.
Methods: A descriptive study with focus group discussions (n = 12 PHNs) and inductive content analysis.
Results: Public health nurses acknowledged that screening for intimate partner violence is part of their responsibilities, even when it is challenging. Barriers to screening included lack of privacy and lack of a common language. PHNs also described difficulties when pregnant women were accompanied by their partners or others during clinic visits, as this limited the possibility for confidential conversations.
Discussion: Public health nurses expressed concern that IPV is often unreported, even when systematic screening is conducted. Many nurses also encountered cultural barriers when addressing IPV. This highlights the need for multilingual screening tools and clear guidelines on how to navigate situations where language barriers or the lack of privacy make communication difficult.
Conclusion: More sensitive and culturally appropriate strategies are needed for the screening of IPV in maternity clinics.